El muchacho de los senos de goma - Iparraguirre, Sylvia (Buenos Aires : Aguilar, Altea, Taurus, Alfaguara, 2007)
A teen struggles to survive, a philosophy professor faces contradictions in his life and a woman is confronted with the pain of death. All three live in Buenos Aires, a city where the poor, abandoned, and scorned all struggle to live.
Keywords: Interpersonal relations -- Fiction; Buenos Aires (Argentina) -- Social conditions -- Fiction